Oxygen extraction fraction is not uniform in human brain: a positron emission tomography study - Hiroshi Ito; Masanobu Ibaraki; Ryo Yamakuni; Motoharu Hakozaki; Naoyuki Ukon; Shiro Ishii; Kenji Fukushima; Hitoshi Kubo; Kazuhiro Takahashi (Journal of Physiological Sciences)
Abstract The regional differences in cerebral oxygen extraction fraction (OEF) in brain were investigated using positron emission tomography (PET) in detail with consideration of systemic errors in PET measurement estimated by simulation studies. The cerebral blood flow (CBF), cerebral blood volume (CBV), OEF, and cerebral metabolic rate of oxygen (CMRO2) were measured on healthy men by PET with 15O-labeled gases. The OEF values in the pons and the parahippocampal gyrus were significantly smaller than in the other brain regions. The OEF value in the lateral side of the occipital cortex was largest among the cerebral cortical regions. Simulation studies have revealed that errors in OEF caused by regional differences in the distribution volume of 15O-labeled water, as well as errors in OEF caused by a mixture of gray and white matter, must be negligible. The regional differences in OEF in brain must exist which might be related to physiological meanings.Article title: Kindly check and confirm the edit made in the article title.I have checked the article title and it is OK as is. Trial registration: The UMIN clinical trial number: UMIN000033382, https://www.umin.ac.jp/ctr/index.htm